La responsabilidad penal de los adolescentes y su finalidad dentro de un estado social de derecho (2015)
The author in this paper aims to emphasize the social problems presented due to the permissibility in repairing the damage and social reintegration that is given to a teenager when he has been responsible for an offense, and the inefficient operation of the criminal law Colombia to call a pedagogical model that should be no school but true exemplary punishment, to avoid future recurrences of criminal behavior because of adolescents. This is sought by comparing the system used in Colombia against the penal system applied in the United States which grants the same means of accountability for offenders of all ages, which has demonstrated an effective remedy of unlawful behavior by practices that comprehensively allow the perpetrator repair damage done and social inclusion under legal standards. Is expected to offer a proposal that serves as a reference to the primary legislator to create standards aimed at meeting the goals of a social rule of law and allow the effectiveness of the system in terms of the integral reparation and restorative care, restorative and transformative responsible for conduct punishable teenager